The Potential of Animal-Assisted Therapy Within the Supervisory Alliance. Issue 1 (2nd January 2017) - Owenby, Bill E.
ABSTRACT: Chandler identified eight generalized benefits of animal-assisted therapy (AAT) for a person's growth. These beneficial areas include (a) motivation, (b) distress tolerance, (c) alternative form of nurturance, (d) physical soothing, (e) genuine acceptance, (f) interactional enjoyment, (g) increased trust, and (h) increased encouragement to overcome barriers. Homestead identified supervision ideals, skills, and barriers within the supervisory alliance. If supervision is negative, this experience may disrupt the supervision relationship, process, and requirements. If not properly addressed, potential harm may come to the supervisee, supervisor, and possibly the client's welfare. This review will identify how these eight areas of AAT may benefit the supervisory alliance to ensure the best care for the supervisee, supervisor, and the client.